The Impact of Economic Growth and Minimum Wages on Poverty in Medan City - Pasaribu, Nurita; Siboro, Hotman; Sidebang, Tamaria Br; Wardana, Vidia (Outline Publisher, 2025)
This study aims to analyze the effect of economic growth and minimum wages on poverty rates in Medan City during the period 2010–2024. Poverty remains a central issue in development despite positive economic dynamics and annual minimum wage adjustments. This study uses a quantitative approach with multiple linear regression methods. Secondary data were obtained from the Central Statistics Agency (BPS), including annual data on economic growth, minimum wages, and poverty rates. The results of the analysis show that economic growth has a positive and significant effect on poverty with a significance value of 0.024, indicating that economic growth has not reached all levels of society evenly. Conversely, minimum wages do not have a significant effect on poverty, indicated by a significance value of 0.880. Simultaneously, both variables do not have a significant effect on poverty (sig. = 0.068). The coefficient of determination (R²) value of 0.361 indicates that the model is only able to explain 36.1% of the variation in poverty rates. This finding emphasizes the need for poverty alleviation policies that are inclusive, integrated, and oriented towards equitable distribution of development results.